Analysis of the Implementation of an Internal Control System Based on the Committee of Sponsoring Organizations of the Treadway Commission Framework in the Preparation of Financial Statements of KSP Kopdit Hiro Heling - Manise, Theresia Vitriana; Dince, Maria Nona; Da Rato, Elisabeth Yessi; Loru, Trifonia Sumelan (Neo Journal of economy and social humanities, 2026)
This study aims to analyze the implementation of an internal control system based on the Committee of Sponsoring Organizations of the Treadway Commission (COSO) framework in the preparation of financial statements at KSP Kopdit Hiro Heling Cooperative. This Research employs a qualitative approach using a case study method, in which data were collected through interviews, observations, and documentation. The results indicate that the implementation of the COSO-based internal control system at KSP Kopdit Hiro Heling has not been fully effective. Several components, including the control environment, risk assessment, control activities, and monitoring, still exhibit weaknesses, while the information and communication component has been implemented relatively well. These weaknesses contribute to cash discrepancies, lack of transparency, and potential unreliability in financial reporting. Therefore, strengthening the internal control system through improving human resource competence, organizational structure, and supervisory functions is necessary to ensure that cooperative financial statements are accurate, transparent, and accountable.